Tashmim al-Kitab al-Madrasi fi Darsi al-Imlai li Tanmiyati Maharah al-Kitabah li al-Mubtadiin li an-Nathiqin Bighairiha - Abdul Hafidz Zaid; Martan Martan; Eko Bowo Wicaksono (Jurnal Internasional Pendidikan Bahasa Arab, 2020)
This research aims to find out the characteristics of the textbook to Imlā lesson to develop the writing skill for beginners non-native speakers, and to scale the validity of the designed textbook. As for the method used for this research is Research & Development, and the methods for collecting the data used are the interview, questionnaire, and documents. To find out the validity of the designed book, the researcher provided the questionnaire to three experts, that is, the expert in the content eligibility of the designed, the expert in the language eligibility of the designed book, and the expert in the graphic eligibility. The results of the search are the presence of the book in the form of the teacher's textbook. The researcher dealt with the characteristics of the textbook in which there are nine units, and in terms of its organization, it started from presenting examples, then explanation, qawā’id, and exercises. As for its validity, it scored good with a percentage score of 84.6%, meaning that the designed textbook can be used with little modification and correction.